Effect of transverse reinforcement on the seismic behavior of diagonally reinforced concrete coupling beams. (1st October 2019) - Han, Sang Whan; Kim, Seung Bum; Kim, Taeo
Highlights: Experiments were conducted for diagonally reinforced concrete coupling beams (DRCBs). The effect of transverse reinforcement on seismic behavior of DRCBs) was investigated. The strength and deformation capacities of DRCBs were strongly affected by the amount of transverse reinforcement. Abstract: Coupled shear wall systems have been more popularly used in high-rise building construction in urban areas due to their efficiency in sustaining lateral loads as well as economic effectiveness. During earthquakes, coupling beams in the coupled wall system act as a seismic fuse element that dissipate most of seismic input energy exerted in the system. Diagonally reinforced concrete coupling beams (DRCBs) have been developed for this purpose. The objective of this study was to acquire test data of DRCBs of with different amount of transverse reinforcement and to evaluate the seismic behavior of these DRCBs. Quasi-static cyclic tests were conducted using seven DRCB specimens with different amounts of transverse reinforcement and different aspect ratios. Four specimens had L n / h of 2.0, whereas it was 3.5 for the other three specimens. The shear strengths of individual specimens were compared to that calculated from the shear strength equation specified in ACI 318-14, and their deformation capacities were compared to those specified in ASCE 41-17. It is observed that the amount of transverse reinforcement in DRCBs played an important role in their shear strength and deformation capacities, indicating that the contribution of transverse reinforcement needs to be incorporated to ACI 318 shear strength equation and ASCE 41-17 model parameters.